1983
DOI: 10.1111/j.1600-0528.1983.tb01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Public views on fluoridation and other preventive dental practices

Abstract: The political nature of fluoridation is due in part to public misconceptions about its purpose, and about its efficacy and practicality in preventing tooth decay as compared with other preventive practices. This paper describes a public opinion survey conducted in Portland, Oregon in May 1980, immediately following a referendum that repealed an earlier vote to fluoridate Portland's water supply. A household interview survey was conducted of 313 Portland residents aged 18 and over. The primary objectives of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…In particular , they would not be able to measure any e ects not directly related to improvements in dental health. For example, the disbene® t generated by violations of freedom of choice has been raised as a general issue in economics (Sen, 1988), and the speci® c violation associated with water¯uoridation has been identi® ed as a potentially important factor (Isman, 1983;Boughton, 1984). Therefore, in order to avoid overlooking such aspects it is necessary to use a measure which can incorporate more than just health bene® ts.…”
Section: I Ec On Om I C E V a L U A T I On S Of D E N T A L C A R Ementioning
confidence: 98%
“…In particular , they would not be able to measure any e ects not directly related to improvements in dental health. For example, the disbene® t generated by violations of freedom of choice has been raised as a general issue in economics (Sen, 1988), and the speci® c violation associated with water¯uoridation has been identi® ed as a potentially important factor (Isman, 1983;Boughton, 1984). Therefore, in order to avoid overlooking such aspects it is necessary to use a measure which can incorporate more than just health bene® ts.…”
Section: I Ec On Om I C E V a L U A T I On S Of D E N T A L C A R Ementioning
confidence: 98%
“…10 For example, Isman 23 found that 64 percent of an adult sample in Oregon obtained dental health information from their dentists, while investigators in Australia found that 65 percent of participants obtained preventive information from their private dental practitioners. 10 Furthermore, dentists regularly encounter a high percentage of the population.…”
Section: Dentists As Sources Of Informationmentioning
confidence: 99%
“…15 The results of a U.S. study conducted in 1980 revealed that only 20 percent of study participants obtained fluoridation information from their dentists. 23 However, in a study of dentists in Minnesota conducted almost two decades previously, Metz 27 reported that approximately one-half of the dentists surveyed stated they discussed fluoridation with many patients. The results of another study showed that although 90 percent of dentists reported discussing water fluoridation with at least a few patients, the majority of those dentists (68 percent) discussed water fluoridation with less than 20 percent of their patients.…”
Section: Dentists As Sources Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the USA and South Africa have shown that many people did not know water fluoridation was intended to prevent tooth decay, although that knowledge was better in higher educated groups and among older people (21–23). Other studies have also found that the public are aware that fluoride can strengthen teeth, because they know that it is added to toothpaste (9, 24). However, no demographic differences in knowledge or attitude were observed between our focus groups.…”
Section: Discussionmentioning
confidence: 99%